Knockout of TMEM206 in mice associated with a loss of corneal transparency - Zi-Jian Yang; Shou-Yue Huang; Yu-Feng Zhou; Shun-Chang Sun (International Journal of Ophthalmology)
AIM: To investigate the role of transmembrane protein 206 (TMEM206) in corneal edema in mice by knockout the TMEM206 gene using CRISPR/Cas9 editing technology. METHODS: TMEM206-knockout mice were generated using the CRISPR-Cas9 system. Variations in ophthalmic pathology were observed using slit lamp microscope and optical coherence tomography (OCT), intraocular pressure (IOP) was measured using a TonoLab Rebound Tonometer, and the ultrastructure of the corneal was observed using a transmission electron microscope. RESULTS: Corneal opacity was observed in 4/18 homozygous TMEM206-/- mice whereas a similar change was not observed in heterozygous TMEM206+/- mice and wild-type littermates. OCT examination showed that the mean central cornea thickness was 125±5.4 µm in 4 homozygous TMEM206-/- mice developed corneal edema and 115±1.2 µm in wild-type mice (t=3.468, P<0.05) at 43wk. The mean IOP was 12.08±0.07 mm Hg in four right eyes with corneal edema and 12.03±0.03 mm Hg in three normal left eyes (P>0.05). Transmission electron microscopy revealed a disruption in the organization of the collagen fibrils in the central part of the cornea in homozygous TMEM206-/- mice. CONCLUSION: TMEM206 is associated with corneal edema which caused organizational disruption of collagen fibrils in corneas of mice.